Effect of rainfall on spatiotemporal variation of hydrochemical and isotopic characteristics of the Coastal Lagoon (Songjiho) and groundwater in Korea - Chanyoung Jeong; Woo-Hyun Jeon; Dong-Hun Kim; Soo Min Song; Jung-Yun Lee; Sung Pil Hyun; Hee Sun Moon (Journal of Hydrology: Regional Studies)
Study region: The Songjiho lagoon, located on Korea’s east coast, is a brackish water body influenced by both freshwater and seawater, resulting in unique hydrochemical conditions. Study focus: This study aimed to assess spatiotemporal variations and gain a comprehensive understanding of the dynamic interactions affecting hydrological processes in the coastal lagoon and groundwater. New hydrological insights for the region: A multidisciplinary approach was used to analyze seasonal hydrochemical variations and mixing processes. The Piper diagram identified three water types: Ca-HCO₃ (inland), Na-Cl (coastal), and Na-HCO₃ (transitional). Principal Component Analysis (PCA) classified hydrochemical characteristics into freshwater-like, saline water-influenced, and runoff-driven groups, revealing complex seasonal ion shifts due to rainfall. Dissolved organic carbon (DOC) and major ions were key indicators of seasonal changes, with rainfall increasing DOC and depleting ions in the lagoon. The Seawater Mixing Index (SMI) identified three coastal aquifer processes: freshwater recharge, fresh-saline mixing, and saline water intrusion. Inland areas exhibited lower ion concentrations due to freshwater recharge, while coastal aquifers experienced depth-dependent seawater intrusion, which weakened in the wet season due to rainfall-induced dilution. The lagoon exhibited the most significant seasonal variation, influenced by river inflow, surface runoff, and hydrodynamic controls. These findings highlight the importance of monitoring seasonal hydrochemical dynamics to manage seawater intrusion risks and ensure sustainable coastal groundwater resources.